PENGARUH PROMOSI ONLINE DAN KEPERCAYAAN KONSUMEN TERHADAP MINAT BELI KONSUMEN PADA E-COMMERCE SHOPEE - Prakoso, Sugih; Setiatin, Tuti (REUGREUG: Jurnal Bisnis Digital, Akuntansi, Kewirausahaan, dan Manajemen, 2025)
This study aims to analyze the influence of Online Promotion and Consumer Trust on Consumer Purchase Interest in e-commerce shopee. The approach used in this study is a quantitative method. The population of this study were students of Linggabuana University PGRI Sukabumi, with a sample of 100 respondents. The data collected were primary data through the distribution of questionnaires to respondents. Data analysis techniques used include instrument validity and reliability tests, as well as analysis prerequisite tests that include normality, multicollinearity, heteroscedasticity, and linearity tests. Data analysis was continued using multiple linear regression. The independent variables in this study are Online Promotion and Consumer Trust, while the dependent variable is Consumer Purchase Interest. The multiple linear regression model obtained produces the equation Y = 6.611 + 0.312 X1 + 0.714 X2, with a constant of 6.611, an Online Promotion coefficient (X1) of 0.312, and a consumer trust coefficient (X2) of 0.174. Based on the t-test, online promotion (X1) shows a partial influence on consumer purchasing interest with a significance value of 0.000 (<0.05). Likewise, consumer trust (X2) has a partial influence with a significance value of 0.01 (<0.05). Simultaneously, Online Promotion and Consumer Trust have a positive and significant influence on Consumer Purchasing Interest. This is proven through the F test in the ANOVA analysis, where the F-count value of 103.695 is greater than the F-table of 3.09, with a significance level of 0.001 (<0.05).